First occurrence of a frog-like batrachian (Amphibia) in the Late Triassic Fleming Fjord Group, central - Jesus, Valerian J. P. (2022)
During the Triassic, Batrachia diverged into ancestors of frogs (Salientia) and salamanders (Caudata). Fossils of Triassic batrachians are rare and found only in a few outcrops, such as the Middle Sakamena Formation of Madagascar (Induan). Only three Triassic taxa have been described, the two early frogs Triadobatrachus and Czatkiobatrachus and the early salamander Triassurus. Here we describe a right ilium, collected in 1991, attributed to the first batrachian from the Late Triassic Carlsberg Fjord Member (Ørsted Dal Formation, Fleming Fjord Group) in the Jameson Land Basin, located in central East Greenland. The fossil specimen only displays the proximal part of a right ilium, missing its shaft. After a thorough comparison with several clades (lizards, temnospondyls, salamanders and frogs), we consider the specimen as a lissamphibian sharing feature with salientians and anurans: squarish acetabular region, deeply concave acetabular surface, laterally projecting acetabular rim, flat mesial surface. It is the youngest Triassic specimen of Batrachia to date and one of the northernmost of the Late Triassic.